Defining the incidence of cutaneous squamous cell carcinoma in coastal NSW Australia. (9th April 2022) - Wilson, Anna; Goltsman, David; Nankervis, Jane; Clark, Jonathan; Gupta, Ruta; Ashford, Bruce
ABSTRACT: Background/Objectives: To describe the incidence of primary cutaneous squamous cell carcinoma in coastal NSW Australia. Methods: The design is a case‐controlled study of reported cSCC from 2016 to 2019 within a defined region of coastal southern NSW. Participants include all reported pathological diagnoses of cSCC in patients greater than 20 years of age. The main outcome measures the incidence and relative risk of cSCC. Results: The age‐adjusted incidence rate of primary cSCC was 856/10 5 /year. Men over 60 years of age had an age‐adjusted incidence rate of 2875/10 6 /year. Histologically diagnosed invasive SCC samples were included using SNOMED clinical term codes. Keratoacanthomas and SCC in situ SNOWMED codes were not included. SCC in situ results was found within the sample analysis and was offset by including one SCC per annum per person. Conclusions: The rates of cSCC are far higher than previously reported and demand a reappraisal of our national management of this disease.